Converting Okara to Superabsorbent Hydrogels as Soil Supplements for Enhancing the Growth of Choy Sum (Brassica sp.) under Water-Limited Conditions - Zhu Jingling (American Chemical Society, 2021)
https://doi.org/10.1021/acssuschemeng.0c02181